The Power of Civilization: The Role of Civilized Cities in Corporate ESG Performance - Qi, Zhenyu; Zhang, Enqi; Wang, Chuncao; Liu, Wei (Frontiers in Environmental Science, 2022)
Civilization, as a kind of ethics, will have its societal impacts contributed by well-integrated members of society. We argued that the government-led construction of a national civilized city will encourage corporate to assume more ESG investments, including social and environmental practices. Based on panel data of Chinese listed corporate, we found that if its residence was rated as a national civilized city, the corporate ESG performance will improve. However, this effect is only significant in environmental practices, which is highly concerned and easy to be quantified by the government. In addition, this positive effect is only significant in state-owned firms with close relationship to the government. The spotlight effect of the media is an essential guarantee for civilized city policies to promote corporate ESG performance. This study confirms the role of the government-led civilized city construction as a soft restraint mechanism in enhancing corporate environmental practices, but also finds the insufficiency in motivating other social duties, which expands the research on the influencing factors of corporate ESG performance.